Comparing sedative effects of epidural bupiv a caine with ropiv a caine on bispectral index during awake phase and general anaesthesia - Muhammad Habibullah, Zakaria (2009)
Combined epidwai/generaJ anaesthesia technique has widely been used in major abdominal, lower limbs and thoracic surgery. Epidural anaesthesia has been shown to produce sedative effect and to reduce the requirements of volatile and IV anaesthetic agents. The aim of this study is to evaluate the sedative effect of epidural anaesthesia between bupivacaine and ropivacaine on the bispectral index (BIS) during awake and general anaesthesia. A prospective, randomized double-blinded ~finical trial was .conducted on 54 patients planned for elective abdominal or lower limbs surgery under combined epidural and general anaesthesia. This was done in a time frame of twelve (12) months at the operation theater of Hospital Universiti Sains Malaysia (HUSM) after approval by the Research and Ethics Committee, School of Medical Science, University Sains Malaysia, Kubang Kerian, Kelantan. The patients were randomly allocated to 2 groups receiving either 10 mls of 0.5% epidural ropivacaine (group R) or the same volume of 0.5% bupivacaine (group B). The BIS measurements during awake phase were performed at 5, 10, 12, 14, 16, 20 and 25 minutes after the epidural injection. General anaesthesia was then induced with fentanyl, propofol and rocuronium and maintained with 2.0% sevoflurane. From approximately 10 minutes after tracheal intubation, the BIS measurements were made at 1 minute intervals for 10 minutes. Amount of sevotlurane administered was adjusted to maintain the bispectral index scale between 40 and 60. There were no significant differences in demographic data among the groups. There was statistically significant mean difference in the BIS values between epidural bupivacaine (group B) and epidural ropivacaine (groul;' R) during awake phase. However, the BIS value during general anaesthesia was not significantly different between two groups. This study also demonstrated that the requirement of sevotlurane was not statistically significant different between two groups. Mean BIS values during awake phase was statistically significant lower in epidural ropivacaine compared to epidural bupivacaine. However, the mean BIS values during general anaesthesia phase between two groups were not significantly difference. The requirement of sevoflumne concentration between two groups during general anaesthesia was not significantly different statistically.